Pembuatan Video Iklan Menggunakan Wondershare Filmora untuk Meningkatkan Consumer Engagement di UMKM Ayam Goreng J&J Kota Malang - Jesy Aprilia L Gaol; Heru Utomo (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The Food and Beverage (F&B) industry continues to grow rapidly, including in Malang City, which hosts various local culinary businesses. Ayam Goreng J&J, a micro, small, and medium enterprise, has served traditional chicken and seafood dishes since 2006. Facing digital competition, the business began optimizing its marketing through Instagram. This study aims to measure the effectiveness of advertisement videos as a digital promotional medium using the AIDA (Attention, Interest, Desire, Action) framework and Consumer Engagement Theory (CET). This action research was conducted in two cycles consisting of planning, action (pre-production, production, post-production), observation, and reflection stages. Questionnaires based on AIDA and CET models were distributed to the business owner, IT and marketing experts, and potential consumers. The results show that the advertisement video effectively increased consumer engagement. In Cycle II, the AIDA score reached 96.48% (Excellent category) and the average CET score was 4.66 (Very High category), with no “Disagree” responses remaining. Additional data also revealed improvements in engagement rate, average watch time, and follower growth on Instagram account @ayamgorengjj. Therefore, creating advertisement videos using Wondershare Filmora proved effective as a digital promotion strategy to enhance consumer engagement for Ayam Goreng J&J’s Instagram business account.